2019
DOI: 10.1111/oik.06166
|View full text |Cite
|
Sign up to set email alerts
|

Complex tactics in a dynamic large herbivore–carnivore spatiotemporal game

Abstract: The spatiotemporal game between predators and prey is a fundamental process governing their distribution dynamics. Players may adopt different tactics as the associated costs and benefits change through time. Yet few studies have investigated the potentially simultaneous and dynamic nature of movement tactics used by both players. It is particularly unclear to what extent perceived predation risk mediates the fine‐scale distribution of large and dangerous prey, which are mostly driven by bottom–up, resource‐re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 69 publications
0
7
0
1
Order By: Relevance
“…Predator movements generate spatial variation in predation risk that can be perceived by prey, which can further respond by modifying their behavior (Gaynor et al, 2019). Prey will for example avoid areas that are highly used by their predators (Simon et al., 2019; Valeix et al, 2009). The distance traveled by predators within their territory could have critical effects on the spatial and temporal distribution of predation risk, since a predator's movement rate strongly determines its encounter rate with prey, which in turn controls its consumption rate (Holling, 1959; Merrill et al, 2010; Pawar et al., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Predator movements generate spatial variation in predation risk that can be perceived by prey, which can further respond by modifying their behavior (Gaynor et al, 2019). Prey will for example avoid areas that are highly used by their predators (Simon et al., 2019; Valeix et al, 2009). The distance traveled by predators within their territory could have critical effects on the spatial and temporal distribution of predation risk, since a predator's movement rate strongly determines its encounter rate with prey, which in turn controls its consumption rate (Holling, 1959; Merrill et al, 2010; Pawar et al., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Previous theoretical (Mitchell & Lima 2002;Mitchell 2009) and empirical (Roth & Lima 2007;Valeix et al 2011;Bosiger et al 2012;Simon et al 2019) studies have suggested that predators and prey play a shell game in which both the prey and the predator would benefit from moving regularly in an unpredictable manner to prevent the other player to learn and then avoid (for the prey) or focus on (for the predator) places where the other player would be. Theoretical studies have however focused on unpredictability of the prey, as they never allowed predators to move somewhat randomly.…”
Section: Discussionmentioning
confidence: 99%
“…Empirical demonstrations of the shell game are only emerging (Simon et al 2019)(but see Laundré 2010), and the optimal level of randomness that prey and predators should optimally use remains unknown. No theory integrating the co-evolution of prey and predator movement strategies has been proposed yet, and we argue this is a fundamental gap in our ability to understand and predict the movement of animals.…”
Section: Introductionmentioning
confidence: 99%
“…Behavioural traits play an important role in predator-prey interactions. Experiments have demonstrated that predators and prey show strong behavioural responses to each other (Gilliam & Fraser 1987;Savino & Stein 1989;Ehlinger 1990;Hammond et al 2007;Simon et al 2019). These responses differ across species and spatial scales, and they are likely the product of strategies that incorporate various information sources from the environment.…”
Section: Introductionmentioning
confidence: 99%